Understanding the seasonal dynamics of phytoplankton biomass and the deep chlorophyll maximum in oligotrophic environments: A Bio‐Argo float investigation. Issue 8 (22nd August 2014) - Mignot, Alexandre; Claustre, Hervé; Uitz, Julia; Poteau, Antoine; D'Ortenzio, Fabrizio; Xing, Xiaogang
Abstract We deployed four Bio‐Argo profiling floats in various oligotrophic locations of the Pacific subtropical gyres and Mediterranean Sea to address the seasonal phytoplankton dynamics in the euphotic layer and explore its dependence on light regime dynamics. Results show that there is a similar phytoplankton biomass seasonal pattern in the four observed oceanic regions. In the lower part of the euphotic layer, the seasonal displacement of the deep chlorophyll maximum (DCM) is light driven. During winter, the chlorophyll a concentration ([Chl a]) always increases in the upper euphotic mixed layer. This increase always results from a photoacclimation to the reduced irradiance. Depending on the location, however, the concentration can also be associated with an actual increase in biomass. The winter increase in [Chl a] results in an increase in irradiance attenuation that impacts the position of the isolume (level where the daily integrated photon flux is constant) and DCM, which becomes shallower. In summer when the [Chl a] in the upper layer decreases along with light attenuation, the DCM deepens and becomes closer to (and sometimes reaches) the nitracline, which enhances the phytoplankton biomass at the DCM. The bio‐optical mechanisms and their relationship to light regimes that are revealed by the time series appear to be generic and potentially characteristic of all of the areas where a DCM forms, which is 50% of the open ocean.